Seed morphology and anatomy and its utility in recognizing subfamilies and tribes of Zingiberaceae. Issue 11 (29th October 2015) - Benedict, John C.; Smith, Selena Y.; Collinson, Margaret E.; Leong‐Škorničková, Jana; Specht, Chelsea D.; Marone, Federica; Xiao, Xianghui; Parkinson, Dilworth Y.
Abstract : PREMISE OF THE STUDY: Recent phylogenetic analyses based on molecular data suggested that the monocot family Zingiberaceae be separated into four subfamilies and four tribes. Robust morphological characters to support these clades are lacking. Seeds were analyzed in a phylogenetic context to test independently the circumscription of clades and to better understand evolution of seed characters within Zingiberaceae. METHODS: Seventy‐five species from three of the four subfamilies were analyzed using synchrotron based x‐ray tomographic microscopy (SRXTM) and scored for 39 morphoanatomical characters. KEY RESULTS: Zingiberaceae seeds are some of the most structurally complex seeds in angiosperms. No single seed character was found to distinguish each subfamily, but combinations of characters were found to differentiate between the subfamilies. Recognition of the tribes based on seeds was possible for Globbeae, but not for Alpinieae, Riedelieae, or Zingibereae, due to considerable variation. CONCLUSIONS: SRXTM is an excellent, nondestructive tool to capture morphoanatomical variation of seeds and allows for the study of taxa with limited material available. Alpinioideae, Siphonochiloideae, Tamijioideae, and Zingiberoideae are well supported based on both molecular and morphological data, including multiple seed characters. Globbeae are well supported as a distinctive tribe within the Zingiberoideae, but no other tribe could be differentiated using seeds due to considerable homoplasy when compared with currently accepted relationships based on molecular data. Novel seed characters suggest tribal affinities for two currently unplaced Zingiberaceae taxa: Siliquamomum may be related to Riedelieae and Monolophus to Zingibereae, but further work is needed before formal revision of the family.